Zein inclusion changes the rheological, hydrophobic and mechanical properties of agar/konjac glucomannan based system. (April 2023) - Qiao, Dongling; Lu, Jieyi; Chen, Zhining; Liu, Xizhong; Li, Mengying; Zhang, Binjia
Abstract: The practical characteristics (rheological, hydrophobic, and mechanical) of biopolymer matrix are essential for its application in food. This work discloses how zein incorporation alters these characteristics of agar/konjac glucomannan (KGM) based matrix. The zein particles formed non-intensive interactions with hydrophilic agar/KGM molecules and thus weakened the chain entanglements in the agar/KGM/zein (AKZ) ternary solutions, which allowed reductions in the zero-shear viscosity (from 4800 to 600 mPa s), sol-gel transition point ( T gel, from 39 to 35 °C) and storage modulus (from about 16000 to ∼1000 Pa) of the resulting AKZ ternary gels. Also, such effects tended to enhance the agar aggregation (zein content: <12%) and the zein crystalline structure (zein content: >12%), reducing the dissolution rate and swelling ability of the acquired AKZ films (dehydrated gels) but increasing their T g (ca. 10 °C higher). The tensile strength and elongation at break of the composite films reached ca. 70–80 MPa and ca. 5%–7%, respectively. The results here may facilitate the development of agar/KGM-based composites (solution, gel or film) with desirable performance. Graphical abstract: Image 1 Highlights: Zein inclusion reduced chain entanglements and viscosity of agar/KGM solution. Zein inclusion reduced the sol-gel transition point of resultant AKZ ternary solution. Zein inclusion enhanced the crystallinity of resultant AKZ ternary film. Zein inclusion reduced the dissolution rate and swelling of AKZ ternary film. Zein inclusion could increase the elongation of resultant AKZ ternary film.